2022
DOI: 10.3390/ijms23105571
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of C2H2 Zinc Finger Gene Family and Its Response to Cold and Drought Stress in Sorghum [Sorghum bicolor (L.) Moench]

Abstract: C2H2 zinc finger protein (C2H2-ZFP) is one of the most important transcription factor families in higher plants. In this study, a total of 145 C2H2-ZFPs was identified in Sorghum bicolor and randomly distributed on 10 chromosomes. Based on the phylogenetic tree, these zinc finger gene family members were divided into 11 clades, and the gene structure and motif composition of SbC2H2-ZFPs in the same clade were similar. SbC2H2-ZFP members located in the same clade contained similar intron/exon and motif patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…There were 218 C2H2 members in alfalfa, and these members had 337 individual C2H2 motifs ( Medicago truncatula ); 134 C2H2 members were identified in Camellia sinensis, which were distributed on 15 chromosomes randomly [ 48 , 50 ]; 79 C2H2 proteins were identified in potato ( Solanum tuberosum ) through hmmsearch and BLASTP in the genome database [ 47 ]. In sorghum ( Sorghum bicolor ), 145 members were identified and distributed on 10 chromosomes [ 30 ]. In this study, 150 members were used as the C2H2 members in maize ( Zea mays ), which covered all of the chromosomes of the reference genome and the splice “B73V4_ctg40”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 218 C2H2 members in alfalfa, and these members had 337 individual C2H2 motifs ( Medicago truncatula ); 134 C2H2 members were identified in Camellia sinensis, which were distributed on 15 chromosomes randomly [ 48 , 50 ]; 79 C2H2 proteins were identified in potato ( Solanum tuberosum ) through hmmsearch and BLASTP in the genome database [ 47 ]. In sorghum ( Sorghum bicolor ), 145 members were identified and distributed on 10 chromosomes [ 30 ]. In this study, 150 members were used as the C2H2 members in maize ( Zea mays ), which covered all of the chromosomes of the reference genome and the splice “B73V4_ctg40”.…”
Section: Discussionmentioning
confidence: 99%
“…As an important transcription factor, C2H2 members have been identified in Arabidopsis [ 5 ], rice ( Oryza sativa ), durum wheat ( Triticum turgidum Durum ), soybean ( Glycine max ), potato ( Solanum tuberosum ), and sorghum ( Sorghum bicolor ) [ 28 , 29 , 30 ], but few studies have identified it in maize ( Zea mays ). Maize is an important crop that is domesticated from wild grass ( Z. mays subsp.…”
Section: Introductionmentioning
confidence: 99%
“…The EPF1 gene of Petunia is the earliest zinc finger protein found in plants with a C2H2 zinc finger structure ( Takatsuji et al., 1992 ). Numerous C2H2-ZFPs have so far been found in plants, including Arabidopsis thaliana 176 ( Englbrecht et al., 2004 ), Sorghum bicolor 145 ( Cui et al., 2022 ), Vitis vinifera 98 ( Arrey-Salas et al., 2021 ), and Panax ginseng 115 ( Jiang et al., 2022 ). The length of the long spacer between the two zinc fingers in plant-specific C2H2-ZFP (Q-type C2H2-ZFP) is different from that of other eukaryotes ( Ciftci-Yilmaz and Mittler, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…The C2H2-type proteins ZFP245 and ZFP179 in Oryza sativa promoted the amount of free proline and soluble sugars, elevated the expression of stress-responsive genes, and enhanced their tolerance to salt and drought stresses [ 15 ]. Under cold environments, ZFP C2H2 directly regulates downstream genes to enhance cold resistance in Sorghum bicolor [ 16 ]. Additionally, ZFP in Glycine soja enhances salt tolerance by maintaining ion homeostasis and removing peroxides [ 17 ].…”
Section: Introductionmentioning
confidence: 99%